2018
DOI: 10.1088/1361-648x/aab5e3
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced Lifshitz and structural transitions in NbAs and TaAs: experiments and theory

Abstract: High pressure Raman, resistivity and synchrotron x-ray diffraction studies on Weyl semimetals NbAs and TaAs have been carried out along with density functional theoretical (DFT) analysis to explain pressure induced structural and electronic topological phase transitions. The frequencies of first order Raman modes harden with increasing pressure, exhibiting a slope change at [Formula: see text] GPa for NbAs and [Formula: see text] GPa for TaAs. The resistivities of NbAs and TaAs exhibit a minimum at pressures c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 34 publications
6
14
0
Order By: Relevance
“…Note that the change only involves discontinuity in the lattice parameters under pressure, which could result from the multiple driving effects or coupling effects. The Lifshitz transition is proposed to describe the change in the Fermi surface topology, which is unrelated to the change of the crystal symmetry. Moreover, pressure-induced anomalies in the c/a ratio, Raman modes, and resistivity can be seen as experimental signatures for the Lifshitz transition, which have been reported in some topological materials. Recently, two Lifshitz transitions were observed in the isostructural compound ZrSiTe, accompanied with a major change in the Fermi surface topology . The proper hydrostatic strain has also been proved to affect the nodal-line lifting in ZrSiSe .…”
Section: Resultsmentioning
confidence: 92%
“…Note that the change only involves discontinuity in the lattice parameters under pressure, which could result from the multiple driving effects or coupling effects. The Lifshitz transition is proposed to describe the change in the Fermi surface topology, which is unrelated to the change of the crystal symmetry. Moreover, pressure-induced anomalies in the c/a ratio, Raman modes, and resistivity can be seen as experimental signatures for the Lifshitz transition, which have been reported in some topological materials. Recently, two Lifshitz transitions were observed in the isostructural compound ZrSiTe, accompanied with a major change in the Fermi surface topology . The proper hydrostatic strain has also been proved to affect the nodal-line lifting in ZrSiSe .…”
Section: Resultsmentioning
confidence: 92%
“…Thus it is an example of hydrostatic pressure induced LT in NaFeAs. Again LT restricts superconducting T c [10,16], hence it could not be raised further with increasing pressure due to occurrence of LT.…”
Section: Fermi Surfaces Of Nafeas and Occurrence Of Lifshitz Transitionmentioning
confidence: 99%
“…For example, Ba 1x K x Fe 2 As 2 near x ∼ 0.5 [10], LiFe 1x Co x As for x ≤ 0.1 [11], K-dosed FeSe thin films [12,13], FeSe single layer grown on SrTiO 3 (FeSe/STO) substrate [14], the intercalated compound (LiFe)OHFeSe [15] etc. Due to multi band nature of electronic structure at the vicinity of the Fermi Level, it would be possible to tune the movement of any one or more number bands downward or upward depending on which high symmetry points in momentum space it crosses the Fermi Level through various external perturbations such as doping [10], pressure [16] or even magnetic field [17] causing Lifshitz transitions. In literature there exists a reasonably well established inter-connection between the LT and the highest superconducting critical transition temperature (T c ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Powder x-ray diffraction measurements on TaAs [26], supported by density functional theory calculations [27][28][29][30], have shown that hydrostatic pressurization above a critical value P c = 14 GPa induces a phase transition from an inversion broken polar Weyl semimetal to an inversion broken nonpolar Weyl semimetal. In this paper, we present a pressure-dependent SHG rotational anisotropy (RA) study of single crystalline TaAs.…”
Section: Introductionmentioning
confidence: 96%